Mobile app for NTU GYM reservation - Chen, Yuxuan (Nanyang Technological University, 2022)
Sports is a significant part in people’s daily lives. Doing sports can benefit people in many ways including reducing stress and anxiety, boosting heart health, losing body fat, and improving appearance as well as mood. In NTU, doing sports is greatly encouraged and thus various sports facilities and fields are provided for staff and students. However, with the prevalence of COVID-19 coronavirus, people’s usual sports habits have been greatly affected: people cannot go to most of sports facilities in NTU without making reservations and strict social distancing and mask rules are executed to control the pandemic. Although NTU have an online reservation web portal for sports facilities, it is not quite user friendly especially for mobile phone users. Nowadays more and more people tend to use their smart phones and mobile applications to access information and handle matters. The number of mobile app downloads worldwide has been increasing constantly from 2016 onward, surpassing 200 billion in 2019. In the most recently measured year, consumers downloaded 230 billion mobile apps to their connected devices, up by more than 63 percent from 140.7 billion app downloads in 2016. [1] The project aims to develop an Android mobile application named NTU GYM for people to make their sports reservations more conveniently through their smart phones. It can also serve as a platform for users to find friends with similar sports interests. This project is mainly developed through Java and XML on Android Studio.